(untitled) - Barbara M. H Strang (New York, 1965)
The first five chapters of this book serve as a basic introduction covering fundamental points about the nature of language, linguistic analysis, phonetics, and structure of English, including a chapter on the phonemic system of standard British pronunciation. The remaining four chapters constitute a brief stetch of the Grammatical function of English words. Each chapter includes exercises
Keywords: english language - phonemics,english language - phonetics,english language - pronunciation,english language - study and teaching